Parâmetros de instabilidade global das estruturas de concreto armado segundo a nova NBR-6118 - Danielle Meireles de Oliveira (2002)
In this work, the parameters of global instability of reinforced concrete structures, according to the draft Brazilian Code NBR 6118 (2000/2001), are studied ( and z instability parameters). Some usual reinforced concrete buildings are analyzed, using the first order theory and the second order theory, to check the level of reliability of theseparameters and the accuracy of z coefficient to evaluate final second order effects. The requirements for global stability of buildings in the draft Brazilian Code for concrete structures are also discussed.